Violin Flash Memory Arrays Now Certified with SAP(R) Sybase(R) Adaptive Server(R) Enterprise to Accelerate Customer Applications in Transaction-Driven Environments (M2 Presswire, 2013)
MOUNTAIN VIEW, Calif. and WALLDORF, Germany -- Violin Memory, Inc. , provider of memory-based storage systems, and SAP AG (NYSE: SAP) today announced that Violin 6000 Series Flash Memory Arrays are now certified for interoperability with SAP(R) Sybase(R) Adaptive Server(R) Enterprise (SAP Sybase ASE) , delivering reliability and accelerated performance across a range of enterprise applications. Used together, these solutions will provide customers with enhanced and simplified solutions that leverage the power of Violin Flash Memory Arrays and business-critical SAP applications to accelerate transaction-driven environments. Additionally, Violin Memory is now an SAP software solution and technology partner in the SAP(R) PartnerEdge(R) program . It will work with SAP to serve new and existing customers, partners and channels to benefit from solutions from Violin Memory and SAP. Violin products are also available in support of the SAP(R) ERP application. Any statements contained in this document that are not historical facts are forward-looking statements as defined in the U.S. Private Securities Litigation Reform Act of 1995. Words such as "anticipate," "believe," "estimate," "expect," "forecast," "intend," "may," "plan," "project," "predict," "should" and "will" and similar expressions as they relate to SAP are intended to identify such forward-looking statements. SAP undertakes no obligation to publicly update or revise any forward-looking statements. All forward-looking statements are subject to various risks and uncertainties that could cause actual results to differ materially from expectations. The factors that could affect SAP's future financial results are discussed more fully in SAP's filings with the U.S. Securities and Exchange Commission ("SEC"), including SAP's most recent Annual Report on Form 20-F filed with the SEC. Readers are cautioned not to place undue reliance on these forward-looking statements, which speak only as of their dates.